2018
DOI: 10.1080/08869634.2018.1431591
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and craniofacial factors associated with changes in mandibular condylar morphology

Abstract: The findings suggest that posterior crossbite and tooth loss are associated with mandibular condyle structural alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
9
0
6
Order By: Relevance
“…This variation in morphology of the condyle may continuously modified throughout life depending on the type of masticatory systems. 19 This study displayed that there was no significant difference between gender and condyle shape, but the round and angled shape were more obvious in females than males, flat was equal in both gender, and the convex shape was common in males, as studies concerning the morphology of condyle by Tassoker et al 17 and Rodrigues et al 18 they have found no relationship between condyle shape and gender while Yalcin and Ararat 16 study showed there was a significant difference between gender and condyle shape with the round shape is rare in both genders, flat type was frequently seen in males compared to females. According to the side convex type is more prevalent to shown bilateral symmetrical shape than other varieties, while Singh and Chakrabarty 14 study showed Rounded type is more prevalent of the sample than other varieties to be symmetrical between left and right side.…”
Section: Discussionmentioning
confidence: 78%
“…This variation in morphology of the condyle may continuously modified throughout life depending on the type of masticatory systems. 19 This study displayed that there was no significant difference between gender and condyle shape, but the round and angled shape were more obvious in females than males, flat was equal in both gender, and the convex shape was common in males, as studies concerning the morphology of condyle by Tassoker et al 17 and Rodrigues et al 18 they have found no relationship between condyle shape and gender while Yalcin and Ararat 16 study showed there was a significant difference between gender and condyle shape with the round shape is rare in both genders, flat type was frequently seen in males compared to females. According to the side convex type is more prevalent to shown bilateral symmetrical shape than other varieties, while Singh and Chakrabarty 14 study showed Rounded type is more prevalent of the sample than other varieties to be symmetrical between left and right side.…”
Section: Discussionmentioning
confidence: 78%
“…Las maloclusiones de clase II podrían actuar como un factor predisponente para la asimetría mandibular si no se realizan tratamientos adecuados (22). Así mismo, la mordida cruzada posterior y la pérdida de piezas dentarias se asocian con alteraciones anatómicas del cóndilo mandibular (23). La RP puede ser utilizada para medir la AM, pero dará como resultados algunos diagnósticos insuficientes (24).…”
Section: La Asimetría Mandibular Diagnósticada a Través De Las Imágenunclassified
“…One of the other factors that affect mandibular condyle structure is tooth loss. Posterior crossbite and tooth loss might be associated with mandibular condyle structural alterations 7 . The other factor is age rising.…”
Section: Introductionmentioning
confidence: 99%